A new approach to the classification of muscle health: preliminary investigations. (30th August 2019) - Thornley, Isobel; Hynd, Jason; Stein, Stella; Butterworth, Mathew; Hind, Karen; Francis, Peter
Abstract: Objective : Upper leg skeletal or lean tissue mass (LTM), strength and muscle quality have emerged as time-sensitive indices of muscular health. The aim of this study was to generate a comparative data set based on these indices, in healthy young ( n   =  30, 29.0  ±  3.0 y old) and older ( n   =  32, 58.7  ±  2.8 years old) adults, in order to evaluate their construct validity in establishing cut-points for muscle health. Approach : Whole body and upper leg LTM was obtained (iDXATM; GE Healthcare, Madison, WI) prior to the assessment of maximal voluntary isometric torque of the knee extensors and flexors (Cybex Isokinetic Dynamometer; Humac Norm, USA). Main results : Peak isometric upper leg torque showed the greatest age-related difference (−29.0%), followed by muscle quality (−19.1%) and upper leg LTM (–9.8%). Significance : Cut-points based on Z and T -scores generated from the young adult mean suggest muscle quality demonstrates the greatest construct validity toward the aim of classifying the muscular health of adults. Data generated from large, representative and sex-specific samples are required to adequately classify the muscular health of adults.